Digitalisasi Al-Quran: Meninjau Batasan Antara yang Sakral dan yang Profan pada Aplikasi “Muslim Pro” - Sukma, Adinda Putri; Nugroho, Wahyu Budi; Zuryani, Nazrina (JURNAL ILMIAH SOSIOLOGI: SOROT, 2019)
ABSTRACT This studyanalyze and explain the boundaries between the sacred and profane in Al-Quran applications, especially Muslim Pro. The approach used in this study is qualitative with descriptive explanatory type and analysed using the sacred and profane theory of Emile Durkheim and Walter Benjamin's thoughton mechanical reproduction. Through the research that has been done, it is known that the differences in treatment between Al-Quran in the form of mushaf or sheets with the Al-Quran digital form in Muslim Pro applications have made the digital Al-Quran lose its sacredness. Ablution rites and prohibitions such as not bringing the Al-Quran to an impure place like a toilet, carelessly misplaced, not reading it too hard so that it can disturb other people, and not being allowed to touch it except in a sacred state are known to disappear along with the appearance of the application Al-Quran especially Muslim Pro. In addition, the existence of advertisements that often appear in the Muslim Pro application shows that the profane dimension is very strong in it. The process of digitalizing the Al-Quran is inseparable from the role of technology that has reproduced it mechanically and eliminated the tradition that surrounded it. The digital Quran in the Muslim Pro application as a literary work has lost its aura and magical power due to being free from the obstacles and various traditions that accompany it. Keywords; Digital Quran, Muslim Pro, rite and prohibition, sacred and profane.